Impact of Corruption Index to Indonesian Rubber (Hs-4001) Export - Hairul Rahman; Unggul Heriqbaldi; Firdan Belado Romadona (MediaTrend, 2022)
This study aims to see the impact of the corruption index which is suspected to be a barrier to Indonesia's rubber exports (HS-4001) to 30 major importing countries during the period 2010 - 2019. The type of data in this study is secondary data in the form of panel data with an estimated fixed effect model (FEM). to see the effect of the independent variables CPIS, ECONS, POPS and FDI on the dependent variable Indonesian rubber exports (HS-4001). The estimation results in this study indicate that the corruption index has no effect on fluctuations in Indonesia's rubber exports (HS-4001) which is caused by the long expiration of rubber products (HS-4001), while the variables of economies of scale and population of scale have a positive effect with different percentages. (2.7% and 49.14%) to Indonesia's rubber exports (HS-4001), for the FDI variable itself has a negative effect on Indonesia's rubber exports (HS-4001) with a percentage of -0.4%.